Using the WHO building blocks to examine cross-border public health surveillance in MENA - Laura Buback; Shayanne Martin; Esbeydy Pardo; Farah Massoud; Jesus Formigo; Atousa Bonyani; Noha H. Farag; Zayid K. Almayahi; Kenta Ishii; Susie Welty; Dana Schneider (International Journal for Equity in Health)
Abstract The introduction of the Sustainable Development Goals by the United Nations has set a global target for achieving Universal Health Coverage, requiring resilient health systems capable of addressing public health emergencies and ensuring health security. Public health surveillance, crucial for detecting and responding to infectious disease outbreaks, is key to building health system resilience. Due to the high levels of mobility and political instability in the Middle East and North Africa (MENA) region, unique challenges arise in cross-border health surveillance. This review aims to highlight the importance of cross-border public health surveillance in strengthening health systems across MENA to achieve equitable health outcomes. A mixed-methods approach was utilized, combining a systematic literature review with semi-structured in-depth interviews (IDIs) involving 28 stakeholders from seven MENA countries. The literature review adhered to PRISMA guidelines, while the IDIs provided qualitative insights into current surveillance practices and challenges. Findings from the literature review and IDIs were triangulated and analyzed using the WHO Health Systems Strengthening (HSS) Building Blocks Framework to identify key challenges and recommendations for improving cross-border surveillance. Results indicate that existing cross-border surveillance systems in MENA face challenges in data collection, analysis, and sharing, with disparities across countries based on income levels and political contexts. Key challenges include delayed and incomplete data sharing, insufficient funding across sectors, inadequate training, inconsistent data definitions, and limited integration of health data for mobile populations. Recommendations emphasize strengthened governance and leadership to facilitate regional cooperation and information sharing, sustainable financing for implementing a One Health approach, utilizing innovative information systems, workforce development to enhance data collection and analysis, and secure supply chains for medicines and vaccines and equitable service delivery for all mobile populations. In conclusion, the WHO HSS Building Block Framework provides a comprehensive approach to assessing and improving cross-border public health surveillance and enhancing health security and equity in MENA. Strengthening cross-border surveillance systems may help MENA countries meet IHR requirements, achieve greater health security, and advance health equity among all types of mobile populations. Despite limitations, the study offers critical insights for improving cross-border surveillance strategies in the region.